The economic and social burden of pediatric cerebral palsy in Spain: a cost-of-illness study - Nova-Díaz, Diana Marcela; Arana-Rivera, Paloma; Sánchez-Iriso, Eduardo; Aguilera-Albesa, Sergio (Frontiers in Public Health, 2025)
BackgroundCerebral palsy (CP) is the leading cause of motor disability in children and a lifelong condition with no cure, imposing a significant economic burden on families and healthcare systems. However, the economic impact of pediatric CP remains underexplored in Spain, hindering the development of cost-effective policies. Cost-of-illness (COI) studies are essential to quantify disease burden and guide resource allocation. This study aims to classify and estimate the economic and social costs of pediatric CP in Spain from a societal perspective, considering healthcare, government, and family burdens. Additionally, it evaluates the caregiving burden experienced by primary caregivers.MethodsA bottom–up, disease-specific COI study was conducted from a societal perspective using data from a population-based epidemiological registry of CP. Data collection included structured questionnaires and administrative records from regional healthcare and government sources, covering a 1-year period. The Zarit Burden Interview was used to assess caregiver burden. The study captures direct, indirect, and out-of-pocket costs, including productivity losses associated with caregiving.ResultsThe study included 148 children with CP (mean age: 9.72) and their primary caregivers (66% female, mean age: 42.97 years). Medical care costs averaged €3,801 (3.72%), while out-of-pocket expenses totalled €7,041 (6.89%), largely driven by complementary and alternative therapies used by 64% of families. Special education represented €8,932 (8.75%), whereas caregiver productivity losses were the largest component (€60,638; 59.37%). The mean annual societal cost per child was €102,135, over thirty times Spain's mean per capita healthcare expenditure. However, using a conservative assumption that valued the caregiver's time at the minimum wage, the social costs would be €70,190 per child. Children with severe motor impairment (GMFCS III–V) had nearly twice the cost of those with milder impairments (GMFCS I–II) (1.96; 95% CI: 1.92–2.01).ConclusionsThe economic burden of pediatric CP is largely driven by caregiving and non-medical costs, highlighting gaps in financial and social support. These findings call for targeted policies to reduce caregiver strain and enhance funding for assistive services, improving equity in CP care. Additionally, comprehensive cost-effectiveness analyses are needed to guide resource allocation and ensure sustainable support strategies.